PENGARUH MOTIVASI KERJA, KEMAMPUAN KERJA, GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERDAGANGAN DAN PERINDUSTRIANKABUPATEN LABUHANBATU - Al Ihsan, Muhammad Ali (Universitas Labuhanbatu, 2021)
This study aims to determine the effect of work motivation, workability, leadership style, and work discipline on employee performance at the Office of Trade and Industry, Kabupaten Labuhanbatu. This type of research in this thesis is a quantitative descriptive method, which is a form of research based on data collected during research systematically regarding the properties of the object under study by linking the relationships between the variables involved, then interpreted based on related theories. The type of data used consists of primary data, namely data obtained directly from research respondents through field questionnaires, and secondary data, namely data obtained in a ready-made form, which has been collected and processed by other parties. The method of data collection was done by listing statements, the sample in this study were employees of the Office of Trade and Industry of Labuhanbatu Regency, totaling 95 people. The results showed (1) simultaneously work motivation, workability, leadership style and work discipline had a positive and significant effect on employee performance at the Office of Trade and Industry, Labuhanbatu Regency. This can be seen from the value of Fount (6.628)> Fable (2.70) with a significant level of 0.000 <0.05. (2) partially work motivation has a significant effect on employee performance at the Office of Trade and Industry in Labuhanbatu Regency, this can be seen from the value of count (2.155)> t table (1.661) with a significant level of 0.004 <0.05. (3) The workability has a significant effect on employee performance at the Office of Trade and Industry in Labuhanbatu Regency, this can be seen from the value of tcount (3.197)> t table (1.661) with a significant 0.002 <0.05. (4) partially significant leadership style on employee performance at the Office of Trade and Industry Labuhanbatu Regency, this can be seen from the value of tcount (2.567)> t table (1.661) with a significant 0.003 <0.05. (5) partially significant work discipline on employee performance at the Office of Trade and Industry in Labuhanbatu Regency, this can be seen from the value of tcount (4.367)> t table (1.661) with a significant 0.000 <0.05. (6) Employee performance at Labuhanbatu Regency Office can be explained by work motivation, workability, leadership style, and work discipline by 19.3% while the remaining 80.7% can be explained by other factors that are not careful in this study.